Design of Plasmodium falciparum PI(4)KIIIβ Inhibitor using Molecular Dynamics and Molecular Docking Methods. Issue 5 (17th February 2017) - Rajkhowa, Sanchaita; Borah, Sapna Mayuri; Jha, Anupam Nath; Deka, Ramesh Chandra
Abstract: Malaria is one of the most devastating infectious diseases which have infected hundreds of millions of people worldwide. Although several anti‐malarial drugs are in clinical use, there is an urgent need for new drugs acting through novel mechanisms of action due to rapid development of resistance. A lipid kinase, phosphatidylinositol‐4‐OH kinase (PI(4)K) type IIIβ has been recently identified as the target of imidazopyrazines. However, due to the absence of a crystal structure of Pf PI(4)KIIIβ, the process of in‐silico drug development has not been possible. Here, we have modeled the plasmodial PI(4)KIIIβ using homology modeling approach. The model has been validated and further, stabilized using molecular dynamics (MD) simulations. A total of 178 compounds were retrieved from PubChem database. These compounds were screened on the basis of hERG liability and toxicity. Molecular docking calculations were performed using two softwares to study the interaction of the selected molecules with the model protein. Docking studies helped us to identify a few molecules with better binding modes. The dynamical movement of five selected molecules were studied and the protein‐ligand interactions were analysed. Our results showed that out of the five molecules, three compounds are stable within the binding cavity of the protein and have the potential to inhibit the Pf PI(4)KIIIβ. Our work provides a strategy for the design of specific inhibitors that could potentially target plasmodial PI(4)KIIIβ and would prove to be instrumental in eradicating malaria. Abstract : Three‐dimensional structure of the Pf PI(4)KIIIβ is model to analyse the characteristics and functional aspects of the protein which would help in the design of newer anti‐malarial drug.